ΓTools: A modular multifunction phantom for quality assurance in GammaKnife treatments. (November 2017) - Calusi, Silvia; Noferini, Linhsia; Marrazzo, Livia; Casati, Marta; Arilli, Chiara; Compagnucci, Antonella; Talamonti, Cinzia; Scoccianti, Silvia; Greto, Daniela; Bordi, Lorenzo; Livi, Lorenzo; Pallotta, Stefania
Highlights: A new modular phantom for QA in Gamma Knife treatments is presented. MR image distortions measurement in a volume comparable to a full volume of a head. dose measurements with gafchromic films in different positions and orientations. continuous development of components that meet new QA requirements. Abstract: Purpose: We present the γTools, a new phantom designed to assess geometric and dosimetric accuracy in Gamma Knife treatments, together with first tests and results of applications. Methods: The phantom is composed of two modules: the imaging module, a regular grid of 1660 control points to evaluate image distortions and image registration result and the dosimetry module for delivered dose distribution measurements. The phantom is accompanied by a MatLab routine for image distortions quantification. Dose measurement are performed with Gafchromic films fixed between two inserts and placed in various positions and orientations inside the dosimetry module thus covering a volume comparable to the full volume of a head. Results: Tests performed to assess the accuracy and precision of the imaging module demonstrated sub-millimetric values. As an example of possible applications, the phantom was employed to measure image distortions of two MRI scanners and to perform dosimetric studies of single shots delivered to homogeneous and heterogeneous materials. Due to the phantom material, the measured absolute dose do not correspond to the planned dose; doses comparisons are thus carried out between normalized dose distributions. Finally, an end-to-end test was carried out in the treatment of a neuroma-like target which resulted in a 100% gamma passing rate (2% local, 2 mm) and a distance between the real target perimeter and the prescription isodose centroids of about 1 mm. Conclusions: The tests demonstrate that the proposed phantom is suitable to assess both the geometrical and relative dosimetric accuracy of Gamma Knife radiosurgery treatments.